A/B Integrations: 7 Lessons Learned from Enabling A/B testing as a Product Feature - Fabijan, Aleksander; Arai, Benjamin; Kohlmeier, Sebastian; Kwong, April; Drake, Andy; Dmitriev, Pavel (2023 International Conference on Software Engineering, 2023)
A/B tests are the gold standard for evaluating product changes. At Microsoft, for example, we run tens of thousands of A/B tests every year to understand how users respond to new designs, new features, bug fixes, or any other ideas we might have on what will deliver value to users. In addition to testing product changes, however, A/B testing is starting to gain momentum as a differentiating feature of platforms or products whose primary purpose may not be A/B testing. As we describe in this paper, organizations such as Azure PlayFab and Outreach have integrated experimentation platforms and offer A/B testing to their customers as one of the many features in their product portfolio. In this paper and based on multiple-case studies, we present the lessons learned from enabling A/B integrations-integrating A/B testing into software products. We enrich each of the learnings with a motivating example, share the trade-offs made along this journey, and provide recommendations for practitioners. Our learnings are most applicable for engineering teams developing experimentation platforms, integrators considering embedding A/B testing into their products, and for researchers working in the A/B testing domain.